The traditional clothing industry of Banjarmasin Sasirangan: A portrait of a local business becoming an industry - Jumriani Jumriani; Syaharuddin Syaharuddin; Ersis Warmansyah Abbas; Mutiani Mutiani; Muhammad Rezky Noor Handy (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Sasirangan is a traditional fabric typical of the Banjar tribal community and has now been developed into an industrial product in Banjarmasin. Sasirangan's business development shows a significant development and it becomes very essential to pay attention to how to maintain its business. This article aims to describe the business operations and distribution patterns in the Sasirangan clothing industry. The qualitative approach was used in this study coupled with data collection through interviews, observations, and documentation. The results showed that Sasirangan fabric products are produced by artisans who work individually or in groups and marketed by traders. Marketing of Sasirangan cloth products uses a direct distribution pattern to consumers, and indirectly uses a merchant intermediary who then resell them to consumers. The collaboration of Sasirangan artisan and traders can be further enhanced to develop a convection industry based on local culture. The findings of this study provide a further description of how local culture-based businesses require support from the government and other parties to maintain business sustainability.JEL Classification J24; M31; O14